LigaSure Impact versus conventional dissection technique in pylorus-preserving pancreatoduodenectomy in clinical suspicion of cancerous tumours on the head of the pancreas: study protocol for a randomised controlled trial - Gehrig, Tobias; Knebel, Phillip; Scheel, Verena; Hinz, Ulf; Seiler, Christoph; Müller, Beat P.; Büchler, Markus W.; Gutt, Carsten N. (Trials, 2011)
The pp-Whipple procedure requires extensive preparation. The conventional preparation technique is done with scissors for dissection and ligatures, and with clips and sutures for hemostasis. This procedure is very time-consuming and requires numerous changes of instruments. The LigaSure™ device allows dissection and hemostasis for preparation with one instrument. Up to now there has been no comparison of the two techniques with regard to operating time and the patients' outcome. It is still unclear which technique has the optimal benefit/risk ratio for the patient.
Gesehen am 10.10.2023